The Second International Symposium on Signed Language Interpretation and Translation Research : Selected Papers - Shaw, Emily; Hunt, Danielle I. J. (Studies in interpretion ;, 2020)
The Second International Symposium on Signed Language Interpretation and Translation Research was a rare opportunity for hearing and Deaf students, researchers, educators, and practitioners to come together and learn about current research in Interpretation and Translation Studies. These selected papers are comprised of research conducted in places such as Australia, Flanders, France, and Ghana, creating a volume that is international in scope. Editors Danielle I. J. Hunt and Emily Shaw have collected papers that represent the advances in the depth and diversity of knowledge in the field of signed language interpretation and translation research. Chapter topics include the use of haptic signals when interpreting for Deafblind people, the role of French Deaf translators during the 2015 Paris terror attacks, and Deaf employees' perspectives on interpreting in the workplace.